Genetic variants in LEP, LEPR, and MC4R explain 30% of severe obesity in children from a consanguineous population. (14th July 2015) - Saeed, Sadia; Bonnefond, Amélie; Manzoor, Jaida; Shabir, Faiza; Ayesha, Hina; Philippe, Julien; Durand, Emmanuelle; Crouch, Hutokshi; Sand, Olivier; Ali, Muhammad; Butt, Taeed; Rathore, Ahsan W.; et al.
Abstract : Objective: Single gene mutations leading to severe obesity have so far been identified in 3‐5% cases in European populations. However, prevalence of these pathogenic mutations has not systematically been examined in specific consanguineous populations. Here we describe the incidence of obesity‐associated mutations through a step‐wise sequence analysis, in a cohort of 73 Pakistani children with severe obesity from consanguineous families. Methods: Initially, all subjects were screened for mutations in coding regions of leptin ( LEP ) and melanocortin 4 receptor ( MC4R ) genes by direct sequencing. Subjects negative for mutation in these genes were screened using microdroplet PCR enrichment and NGS. Genomic structural variation was assessed by genotyping. Serum leptin, insulin, and cortisol were determined by ELISA. Results: Among 73 children with severe obesity (BMI SDS > 3.0), we identified 22 probands and 5 relatives, carrying 10 different loss‐of‐function homozygous mutations in LEP, leptin receptor ( LEPR ), and MC4R genes, including 4 novel variants. Hypercortisolemia was significantly emphasized in LEP mutation carriers. Conclusions: The prevalence of pathogenic mutations in genes known to directly influence leptin‐melanocortin signaling is 30% in our cohort. The results of this study emphasize the desirability of undertaking systematic and in‐depth genetic analysis of cases with severe obesity in specific consanguineous populations.